Characterization of the complete mitochondrial genome of Ageratum conyzoides - Luo, Ze-Ping (Mitochondrial DNA B Resour, 2019)
As a pharmaceutical plant with multi-bioactivity, Ageratum conyzoides appears to be a valuable agricultural resource. In this study, the complete mitochondrial (mt) genome of A. conyzoides was sequenced through Illumina sequencing method, and the mt genome was recovered after de novo assembly and annotation. The results showed that the 219,198 bp mt genome has a total of 52 genes, including 30 protein-coding genes, 3 rRNA genes and 19 tRNA genes. The overall GC content of this mitogenome is 45.4%. By phylogenetic analysis using maximum-likelihood (ML) method, A. conyzoides showed the closest relationship with Diplostephium hartwegii in the family of Asteroideae.